Comprehensive technical analysis of a kickboxing fight in K1 format based on observation - Niewczas, M.; Wasacz, W.; Chwala, W.; Palka, T.; Sobilo-Rydzik, E.; Ambrozy, T.; NEMÁ, K.; Rydzik, L. (Baltic Journal of Health and Physical Activity, 2024)
Introduction: Observation and specialized analysis of confrontations in combat sports are fundamental for introducing corrections in training programs and for modifying the individual technical-tactical profiles of athletes in these types of activities. These actions comprehensively assess the progress of sports activities, ultimately inspiring and guiding the direction of training in sports clubs. The aim of this study was to analyze and assess the level of the offensive structure of Kickboxing sport fights in the K1 format, in terms of global simulated sparring, in selected thematic sets.